Asceticism in some Indo-European traditions - Allen, N (2005)
The paper compares the periods of asceticism or privation that precede journeys to heaven, or transitions to some other sort of salvation, in four narratives: Mahabharata book 3, Odyssey books 5-6, the Wasting Sickness of Cuchulainn, and the story of the Buddha's enlightenment. It is argued that all derive from an early Indo-European proto-narrative, probably marked by the pentadic ideology, to which the Sanskrit epic offers the closest approximation.